Alternativas farmacológicas para a resistência parasitária múltipla em rebanhos de ruminantes: uma nova abordagem - Cezar, Alfredo Skrebsky (2010)
Infections by gastrointestinal nematodes are among the main diseases of the ruminants around the world. These infections cause - in their clinical or subclinical courses a decrease of the productivity of the herds, thus, the economic viability of the ruminant farms is directly related to an adequate control of these parasites. Although the benefits of the use of several practices of alternative control of parasites are proven and, despite of that these practices have been improved through the years, in general, the use of efficacious antiparasitic drugs is imperative to control satisfactorily the helminths of the ruminants. However, the development of parasite resistance to these drugs has become common and, in some cases, parasitic populations are multiple resistant to several classes of anthelmintics and endectocides, and it makes very difficult to control the helminthosis adequately. In this study are shown some experiments conducted with the aim of to find ways to restore the efficacy of the treatments, for recovering the usefulness of active ingredients for which the gastrointestinal nematodes of ruminants became resistant. Efficacy tests of the drugs were made using Fecal Egg Count Reduction Tests (FECRT) and larvae cultures, for the identification of the genus of nematodes existing, before and after the treatments. We evaluated the anthelmintic action of high concentrated (long acting) drugs, overdoses (high dosages), commercial combinations of drugs and combinations of chemicals, formulated with basis in previous efficacy tests for each active ingredient alone. These combinations, done from drugs sold separately, gave us the best results. Based in these observations, we are proposing a new approach regarding helminth control in multi-resistant populations, by using combinations of drugs with different mechanisms of action on the parasites, and taking advantage of the efficacy tests, performed before the choose of drugs, and then, to prove the results obtained with the combinations done particularly for each herd.